Feasibility study on Pinoy Cafe - Lazarte, Ma. Norma; Leano, Genee Renelle; Salvania, Marissa
Coffee is one of the most common beverages among Filipinos. In fact, there is an evident increase in coffee consumption over the years. In addition, going to coffee shops is also becoming a part of the Filipinos' lifestyle especially the coffee lovers. In spite of the increased number of coffee shops all over the country, people from Meycauayan Bulacan travels a long way before they can get a cup of their desired coffee. This is because there is no coffee shop in Meycauayan City. This study aims to determine the feasibility of putting up a coffee shop in Meycauayan Bulacan to make it more accessible to the residents of the area. Also, the new business will provide new job openings for the Bulakenos. To determine the feasibility of a new business venture, it is important to perform market analysis, technical analysis, organizational study, financial study, and social profitability analysis. For the market analysis, the need was first identified and the product concept to meet the need was designed. Also, product marketability was analyzed and the desired target market for the product was defined. Necessary data to support the analysis were gathered. Finally, the forecast of demand was determined and expected revenue was estimated. The market analysis showed that the business is feasible. For the technical study, production alternatives were determined. Also, the demand, inventory level, process and schedule were identified. Capacity planning was also performed. The input requirements, space requirements, layout, location and facilities requirement were analyzed. Finally, total costs were estimated and the best alternative was selected. The business was found to be technically feasible. Results of the market and technical study were used to perform the financial analysis. The required capital investment was estimated. This includes the equipments needed in the shop and the start up costs. Working capital was also identified which includes raw materials, utilities and transportation allowance. Cash flows and balance sheets were made and important monetary figures such as net present value of money, IRR and MARR were computed. The expected payback period was also determined. The results showed that the project was financially feasible. The three important parts of the feasibility study namely, market, technical and financial analysis generally suggests that the new business venture of putting up a new coffee shop at Meycauayan City is feasible.